Optimalisasi Layanan Bank Untuk Meminimalkan Ketidakpuasan Nasabah Mengadopsi Internet Banking - Ronny Ronny (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2018)
The study aims to identify factors contributing in customers’ dissatisfaction in using the internet banking and analyze bank's efforts in minimizing customer dissatisfaction. Data were collected by interview from 20 customer informants and 3 bank official informant in Indonesia within the scope of internet banking management duties. Data analysis was performed by using qualitative approach. Customer dissatisfaction using internet banking include difficulties in operating; unbalanced internet banking access; security concerns; lack of adequate resources; and incomplete internet banking features. There are two determinants of customer dissatisfaction in using internet banking including internal factors and external factors. Internal factors include customer knowledge, customer learning abilities, and resource capabilities. External factors include technology and service performance. The optimization of bank services to minimize customer dissatisfaction is directed to four factors: Customer Involvement; Business Intelligence; Infrastructure of Technology and Human Resources; Socialization and Education.